Determinant of Financial Ratio Analysis to Financial Distress - Setya Ayu Arini; Yuli Chomsatu Samrotun; Endang Masitoh (Jambura Science of Management, 2021)
In this new era bussines world is growing rapidly so that the emergence of many new companies. However, to be the market leader, the company must be able to manage the financial aspects well, so that the company does not have financial difficulties. The research aims to analyse the effects of liquidity ratios, activity ratios, profitability ratios, leverage ratios on the financial difficulties of textile and garment companies listed on the Indonesia Stock Exchange in the period 2018-2019. The object in this study used samples of 40 samples on textile and garment companies listed on the Indonesia Stock Exchange in the period 2018-2019 using sampling techniques purposive. The methods used in this study are some of the processed linear regression analyses using SPSS 25. Based on this study shows that liquidity is influential but not significant to the financial distress. The activity has significant effect on financial distress. Profitability has significant effect on financial distress. Leverage is influential but not significant to the financial distress.